Drug Interactions in Dermatological Practice. What Should be Considered when Treating Patients with Multimorbidity? - Woroń, Jarosław (Dermatology Review/Przegląd Dermatologiczny, 2025)
In dermatological practice, physicians are increasingly encountering patients with multimorbidity who are undergoing polypharmacy. This requires an understanding of the potential interactions between patients’ existing medications and the prescribed dermatological pharmacotherapy. Data from registries of drug-induced complications indicate that adverse effects commonly associated with adverse events often involve medications used in polytherapy. This article compiles the most frequent interactions encountered in dermatological practice.